Faktor-faktor Yang Mempengaruhi AHH Provinsi Bali - Luh Dita Darmayanti; Surya Dewi Rustariyuni (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2019)
The degree of public health can be measured by looking at the amount of Life Expectancy (AHH). AHH is the result of calculating projections often used as one of the People's Welfare Indicators (IKR). Assuming a declining trend in infant mortality rates (IMR) and changes in the population's age composition, the objectives in this study are: 1) to analyze the effect of income per capita, government spending in education, and health simultaneously affect life expectancy in Bali Province / City in the 2011-2017 period and 2) to analyze the effect of per capita income, government spending the education and health sector influences the life expectancy in the Regency / City of Bali Province in the 2011-2017 period. The data used in this study is secondary data in 2011-2017. This study uses Multiple Linear Regression analysis techniques used to process classical assumption test data using Eviews 9. The results of this study stated that the variable income per capita (X1), government expenditure in education (X2), and government expenditure in health (X3) simultaneously affected the life expectancy (Y) in districts/cities in Bali Province. Partially per capita income has a positive and significant impact on life expectancy. Government expenditure in education and government expenditure in health does not affect life expectancy in Bali Province districts/cities.